Enhancing Teacher Training Quality through Transversal Skills: A Case Study of CRMEF Sidi Kacem - Toufik Faik; Abdelaziz El Hammouchi (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: To support Morocco's growth, the education sector must prioritise improving teacher qualifications through higher standards in training and professional development, focusing on transversal skills and modern, tech-integrated methodologies. Method: The study employs a combination of interactive research methodologies, including questionnaire-based data collection and content analysis, to interpret the results. These methodologies allow for an in-depth evaluation of the current state of teacher training and the integration of transversal skills into professional development programs. Result: The findings stress the importance of providing teacher trainees with transversal skills for critical reflection, professional growth, and improved teaching outcomes, while urging educational systems to move beyond traditional methods and address gaps in teacher training programs with targeted interventions. Conclusion: Integrating transversal skills into the curriculum is essential to enhance teacher training in Morocco. The shift towards innovative, skill-based teaching methodologies will better prepare educators for the challenges of modern classrooms, ensuring they are equipped to contribute effectively to Morocco's educational advancement. Contribution: This study provides insights into improving teacher training programs through transversal skills and recommendations for interventions that can equip teachers with the skills necessary to meet evolving educational demands, supporting Morocco's efforts to improve its education sector in line with global trends.